In media(s)res - Strujić, Jure (Zbornik radova međunarodnog teološkog skupa KBF-a u Splitu, 2018)
The Church, in her mission of spreading the Good News, has been continually searching for new ways of proclamation in encounter with various cultures, using also the means of communication. In the beginning, she approached the media with caution, opposition and suspicion, viewed them as rivals; then started to accept them as co-workers, to finally use them as a means of evangelization recognizing a new life area that is in need of evangelization. In order to better understand this developmental path, it is necessary to observe it in the context of historical circumstances and cultural setting of a particular period. The process of adjustment, cooperation and coexistence between the Church and media have been still developing, since media have been greatly changing in terms of their potential and influence, calling for new responses, standpoints and ways. It would be interesting to present the relationship between the Church and media through history, especially after the invention of the press, film, radio and television, and ultimately the Internet as a basis of a true revolution of communication possibilities manifested in the creation of virtual reality. The Church’s attention on media and new forms of communication gained a new impetus with the Second Vatican Council Decree Inter Mirifica as well as with the papal messages on the occasions of the World Day of Social Communications. These messages offer an interesting overview of the Church’s opening to media, bringing significant theologicalpastoral guidance to believers and to media workers. They are a sign of the Church’s concern for a complete development of man and society. Over the past two decades, in their messages, popes especially speak about the Internet, social networks, new forms of witnessing and evangelization of the digital continent, not failing to point to the problems, difficulties and dangers associated with new media.